ANALYSIS OF FACTORS INFLUENCING NON OIL AND GAS EXPORTS IN CENTRAL JAVA JANUARY 2015 - JULY 2019 - Khairani Pambudhi Utami; Vita Kartika Sari; Faiza Husnayeni Nahar (Journal of Applied Economics in Developing Countries, 2021)
The purpose of this research are: 1) To find out the effect of inflation on non-oil exports in Central Java in January 2015 - July 2019, 2) To find out the effect of foreign exchange rates on non-oil exports in Central Java in January 2015 - July 2019, 3) To find out the effect of BI rate on non-oil exports in Central Java in January 2015 - July 2019. The data used in this study are quantitative data in this research of time series data on non-oil and gas exports in Central Java, Central Java inflation, USD foreign exchange rates against Rupiah, and BI Rate in 2015 - July 2019 obtained through the official website of each institution. Analysis of the data used is multiple linear regression which is used to know the effect of the independent variable on the dependent variable. From the results of research conducted by factors affecting non-oil exports in Central Java, the conclusion is inflation, foreign exchange rates and the BI rate partially affect non-oil and gas exports in Central Java in January 2015 - July 2019. Simultaneously inflation and the BI rate have a negative effect on non-oil exports in Central Java in January 2015 - July 2019, and foreign exchange rates have a positive effect on non-oil and gas exports in Central Java in January 2015 - July 2019.Keywords: Export; Inflation; Exchange Rates; BI Rate